Pertumbuhan dan Produksi Tiga Varietas bawang Merah (Allium ascalonicum L.) Pada Pemberian Beberapa Jenis Pupuk Organik di Tanah Terkena Abu Vulkanik Sinabung - Ernika Septyma Br Pardede; Mariati Mariati; Rosita Sipayung (Universitas Sumatera Utara, 2015)
The aim of the research was to identify the influence of several types of organic fertilizer on the growth and yield of three shallot varieties on the land exposed by Sinabung volcanic ash. The research was conducted at the experimental field of Agricultural Faculty, Sumatera Utara University which about ± 25 metres above sea level, begun from April up to August 2014. The experimental design was randomized block design with 2 factors, replicated three times. The first factor was three shallot varieties i.e : V1 (Bima Brebes), V2 (Crok Kuning), V3 (Samosir) and the second was several types of organic fertilizer i.e : P0 (without fertilizer = control), P1 (palm oil fruit bunch), P2 (rice husk ash), and P3 (cow manure). Parameters observed were shoot length, leaves number, tillers number, clove number, harvesting age, and fresh and dried weight bulb per sample. The results showed that all parameters observed were significantly affected by three shallot varieties, meanwhile only harvesting age, and wet and dry weight bulb per plot were significantly affected by several types of organic fertilizer. There was no interaction between both treatments.Keywords: varieties, organic fertilizer, volcanic ash, shallot